Conversion of strontium hydroxyapatite nanopowders to porous scaffolds for bone implant application - Sopyan, Iis; C. M., Mardziah; Koay Mei, Hyie; N. R., Nik Roselina (Trans Tech Publications Ltd., Switzerland, 2014)
The fabrication of strontium hydroxyapatite (SrHA) porous scaffolds was accomplished by using polymeric sponge method. To prepare the porous samples, the synthesized SrHA nanopowders were mixed with distilled water and appropriate amount of dispersing agent followed by drying in the ambient air and sintering at 1300°C. The compressive strength of the materials was strongly influenced by the porosity, while there was almost no dependence on the crystallinity of the powders since XRD patterns showed high crystallinity of HA phase for all porous samples. Morphological evaluation by FESEM revealed that the SrHA scaffolds were characterized by macro-micro interconnected porosity, which replicates the morphology of the cancellous bone. Compression test on the porous scaffolds demonstrated that doping 10 mol% of strontium in HA has increased the compressive strength by a factor of two compared to the undoped HA with 1.81±0.26 MPa at 41% porosity.